PENGARUH RASIO KEUANGAN TERHADAP PERUBAHAN RETURN SAHAM PADA PERUSAHAAN PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Prasetyo, Yogi Agung; Kusuma, Desta Rizky (Universitas Ahmad Dahlan, 2017)
This study aimed to examine the effect of financial ratios on changes in stock returns in 2010-2014. Objects of this study are plantation company listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling method while data analyst method used multiple linear regression. The results showed that the variable of Total Asset Turnover (TAT) and Return On Assets (ROA) has positive effect on changes in stock return, while variable Current Ratio (CR), Debt to Equity Ratio (DER) and Price Earning Ratio (PER) has no effect on retun stock.